Effect of yoga on intra-ocular pressure in patients with glaucoma: A systematic review and meta-analysis - Dipak Chetry; Jayvindra Singh; Archana Chhetri; Vinod Kumar Katiyar; Daya Shankar Singh (Indian Journal of Ophthalmology, 2023)
Glaucoma is the second leading cause of blindness in the world, with an estimated 57.5 million people suffering from glaucoma globally. Treatment of glaucoma focuses on lowering intra-ocular pressure to prevent progression of visual field defects, which is the only proven method for treating this disease. Yoga practices are believed to lower intra-ocular pressure in the eyes and prevent further damage in patients with glaucoma. Therefore, this systematic review was planned to explore the available scientific studies on yoga and intra-ocular pressure in glaucoma patients. PubMed, Cochrane Library, and Google Scholar were the basis for the investigation of the literature. The Jadad Scale was used to assess the quality of included clinical trials, and the JBI Critical Appraisal Checklist was used to assess the quality of included case studies. Based on the quality assessment and eligibility, six studies on yoga and intra-ocular pressure in glaucoma patients carried out between 2007 and 2021 were included in the final review. The results showed a reduction in intra-ocular pressure in patients with glaucoma through Jyoti-trataka (gazing steadily on a point or candle flame) and some other slow yogic breathing techniques, whereas studies on inversion Asanas (yoga postures) showed a rapid increase in intra-ocular pressure soon after starting. The three high-quality RCTs included in the meta-analysis showed a greater improvement in intra-ocular pressure in the yoga groups in both eyes than in the control groups; however, there were some limitations related to a small sample size, study quality, a long-term follow-up period, and variations in the yoga practices. Therefore, further studies with larger sample sizes and long-term follow-up are needed to overcome the limitations for a better understanding.